MISCONCEPTION ANALYSIS IN TERMS OF STUDENT LEARNING STYLES - Winda Rahma Fauziah; Arif Muchyidin (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to determine students' misconceptions in social arithmetic material when viewed from student learning styles. The population in this study was 28 students of class VII F MTs Negeri 5 Cirebon. The research form used in this study is qualitative research, with a research strategy that is a case study. Data collection techniques used were 1) the observation method, 2) the tests method, 3) the questionnaire method, 4) the interview method is conducted for students who experience misconceptions after adjusting to the student's learning style. The results of this study are 1) Students who have a visual learning style do not experience misconceptions in mathematical concepts, but students experience misconceptions in the process of counting and translation. 2) Students who have auditorial learning styles, there are no misconceptions in mathematical concepts, but students experience errors in the final calculation process. 3) Students who have kinesthetic learning styles it is suspected that students have conceptual misconceptions because students do not understand the concept of the process including students who do not understand the mathematical formulas and values that must be used and students do not understand calculations. In general, the causes of misconceptions in students who have visual learning styles, auditory and kinesthetic, are derived from student understanding and teacher learning methods.